Backup distance protection coordination for three terminal HV transmission line considering main protection failure - Mohd. Razali, Mohd. Razani (2021)
The protection system scheme in transmission line is very important to maintain security and reliability of power system. This research will focus on the protection scheme at the three terminal transmission line such as 132kV and 275kV that implement in Malaysia utility and propose a new distance protection system scheme. The backup protection schemes in Malaysia utility has a higher fault clearing time. This research will focus on backup protection operation of three terminal overhead transmission line for all condition with considering main protection fail, DC supply fail or communication fail. Therefore, this study will propose and improve the backup protection scheme, two components will consider which are fault clearing time and distance relay zone configuration. Each improvement has own philosophy and concreate reason to determine advantages for backup protection scheme in three terminal transmission line. The effect for improvement need to ensure time coordination did not overlap with others scheme. To analyse existing and new protection scheme in this study, ETAP software will be use. All decision of fault clearing time and zone coverage can generate by ETAP simulation. The propose method able to help utility to have better fault clearing time and zone of coverage.